English Grammar : (Video Aided Instruction, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! Adjectives and adverbs let us add descriptive information to nouns, pronouns, and verbs to make our sentences more colorful and interesting. But many of us make mistakes when using modifiers. With this informative program, you'll learn how to use modifiers correctly and effectively - even when making comparisons with superlatives! So don't let mistakes in English grammar embarrass you - now you can eliminate them from your speaking and writing forever. Let Video Aided Instruction be your guide! One DVD/1 Hr. 35 Mins. Item #VAI-1078. Volume 7 of Video Aided Instruction's 10-Volume English Grammar Series.